وقف النقود في تمويل مؤسسة ACT في إندونيسيا: دراسة فقهية تحليلية : Cash Waqf for Financing ACT Foundation in Indonesia: A Juristic and Analytical Study - كيرين أكبر; فاطمة كريم (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص وقف النقود من أنفع نوع الوقف في الأعمال الإغاثية. ويهدف هذا البحث الكشف عن وقف النقود في تمويل مؤسسة ACT وطرق استثمار وقف النقود عند المؤسسة. وبالتالي، أنشطة الإغاثة تقتضي إلى صورة توزيع الوقف باستخدام النقود لحفاظ على بقاء العين الموقوفة واستمرار منافعها. استخدم الباحث المنهج الاستقرائي في التعامل مع الأدلة الشرعية والمعلومات والبيانات والتفاصيل فيما يتعلق بوقف النقود. ثم المنهج التحليلي وذلك بتحليل موضوع وقف النقود بكافة جوانبها الشرعية وشرحها ويستنبط منها حتى يوضح الأمر والحكم عن مشروعية وقف النقود وصلاحيته لتمويل المؤسسة الإغاثية. من خلال تنسيق ما بين النظرية والتطبيق، قام الباحث بالدراسة الميدانية بمقابلة المسؤولين في المؤسسة والخبراء وذلك لتأكد من الموافقة في ممارسات واستخدام وقف النقود وكشف طرق الاستثمار لأجل الحصول على منافع وقف النقود. يظهر أن وقف النقود صالحة لتمويل المؤسسة الإغاثية وأنشطتها ولاستغلالها لغرض الاستثمار والحصول على الريع والمنافع. Abstract Cash waqf is the most useful waqf instrument to be used in humanitarian institutions. This research aims to analyze cash waqf and its expedience in financing humanitarian relief institutions (ACT Foundation) and investment methods in the foundation. Thus, humanitarian activities necessitate a form of money distribution to preserve the continuation of its benefits. The researcher used inductive approach in evaluating legal evidences, information, data and details regarding cash waqf. Furthermore, analytical approach was used to analyze and explain the legal aspects of cash waqf and verify its legality and validation to finance humanitarian institutions. By integrating theory and practice, the researcher conducted a field study by interviewing officials in the institution to ensure that the practices are in accordance with Islamic jurisprudence. Also, the research was done to expose investment methods to gain benefits of cash waqf. It can be concluded that the cash waqf is allowed to finance the activities of humanitarian institution as well as being invested to obtain further benefits.